Identification of Typical Functional Groups in Organic Molecules in Absorption Spectroscopy - Dr Sunil Bhatt (Genius Journals, 2022)
Spectroscopy is one of the many significant techniques that are employed in the study of physical phenomena. The term "spectrometre" refers to the devices that are utilised in the process of determining the spectra of various chemicals. They are utilised on the compound itself, and there is also the potential for them to be utilised in the analysis of the fragments that are acquired during the degradative process. There are many other kinds of spectroscopy, including ultraviolet, infrared, visible electron spin resonance, nuclear magnetic resonance (NMR), and mass spectroscopy; however, absorption spectroscopy only applies to ultraviolet, visible, and infrared spectroscopy. Molecules that contain double or triple bonds have stable excited states that, when stimulated, give rise to spectra in the near ultraviolet range. As a result, the presence of such a spectrum assists us in detecting and determining the presence of unsaturation. Molecules that are saturated with hydrocarbons, alcohals, ethers, and other substances are see-through in the near ultraviolet. Compounds like acetone and acetic acid, which only have a single multiple bond, are examples.
Keywords: Organic; Molecules; spectrometer; Absorption